Contradiction Between Supply and Demand of Logistics Talents Training and Teaching Reform in China - Zhong Zheng; Liwei Li; Ganglan Wei (Advances in economics, business and management research/Advances in Economics, Business and Management Research, 2021)
With the continuous emergence of new technologies, new models and new methods, new requirements have been put forward for the training of logistics talents. This paper makes a comprehensive analysis of the supply and demand of logistics talents in China, combines the demand of logistics talents in the new era and new economic environment. This paper studies the contradiction between supply and demand from the aspects of quantity, quality, industry structure and new economic environment of logistics talents. On this basis, this paper studies the strategies to alleviate the contradiction between supply and demand of logistics talents, and puts forward the reform strategy of logistics construction and development of logistics specialty, in order to provide beneficial exploration for the construction and development of logistics major.
Keywords: Innovative Educational Techniques